Timelines associated with the neonatal jaundice care cycle and assessment of caregiver satisfaction - Noguera, Luis Eduardo; Camacho-Cruz, Jhon; Vásquez-Hoyos, Pablo; Suarez-Cuellar, Cristian Camilo; Morales-Lombo, Ana Maria; Rivera, Lia Marcela; Castillo-Jaimes, Ana Maria; Parra-Riveros, Helien; Acelas-González, Gabriel Esteban (Universidad y Salud, 2025)
Introduction: Neonatal hyperbilirubinemia is a major health problem, a common cause of morbidity. Worldwide, it affects up to 60% of term newborns. Its diagnosis is by means of serum bilirubin levels, which is associated with certain disadvantages, especially in terms of discomfort related to delayed results. Objective: To evaluate the relationship between caregiver satisfaction and the time associated with the cycle of care for the diagnosis of neonatal jaundice. Materials and methods: Cross-sectional observational study, neonates with clinical evidence of jaundice were included. Demographic data were collected, a satisfaction survey was applied to evaluate the level of caregiver satisfaction, and the times associated with the cycle of care from the moment of admission to the medical procedure were recorded. Results: A patient flow analysis was performed, and it was found that waiting time is significant, especially in obtaining laboratory results. Caregivers’ satisfaction with waiting times influences their overall perception of service quality. Conclusions: The potential implementation of new diagnostic instruments could generate added value to the service by speeding up medical decision making.